2020
DOI: 10.1186/s12879-020-4926-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of post-exposure prophylaxis practices to improve the cost-effectiveness of rabies control in human cases potentially exposed to rabies in southern Bhutan

Abstract: Background: Rabies is endemic in southern Bhutan, associated with 1-2 human deaths and high post exposure prophylaxis (PEP) costs annually.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 20 publications
(42 reference statements)
1
10
2
Order By: Relevance
“…Nonetheless, in India still, another study reported a higher rate (58%) than ours though there was a significant rural-urban divide with the former performing worse [39]. This, combined with the 7% -45% prevalence of wound washing with soap and water in Kenya and Ethiopia respectively [40,41], is evidence of how…”
Section: Characteristicscontrasting
confidence: 42%
See 1 more Smart Citation
“…Nonetheless, in India still, another study reported a higher rate (58%) than ours though there was a significant rural-urban divide with the former performing worse [39]. This, combined with the 7% -45% prevalence of wound washing with soap and water in Kenya and Ethiopia respectively [40,41], is evidence of how…”
Section: Characteristicscontrasting
confidence: 42%
“…Nonetheless, in India still, another study reported a higher rate (58%) than ours though there was a significant rural-urban divide with the former performing worse [ 39 ]. This, combined with the 7% - 45% prevalence of wound washing with soap and water in Kenya and Ethiopia respectively [ 40 , 41 ], is evidence of how the practice varies across communities. It may also indicate variations in the coverage and uptake of health education interventions across societies.…”
Section: Discussionmentioning
confidence: 99%
“…This poses very few risks of rabies since all exposures are assured of getting the vaccine. However, this leads to unnecessary costs associated with PEP as observed in some studies [22,33]. Further, just like some clinicians explained in this study, there is a tendency for patients to demand administration of the ARV.…”
Section: Inadequate Health Education and Patient Counselingmentioning
confidence: 63%
“…PLOS ONE [21] and Bhutan [22]. Rabies risk assessment must be improved since Uganda is a rabiesendemic country where all dogs are taken to be potentially carrying the rabies virus.…”
Section: Inadequate Health Education and Patient Counselingmentioning
confidence: 99%
“…The educational outreach drives should include such vulnerable groups in their ambit. Further, the lack of application of preventive practices for bite wound management or PEP compliance could be attributable to little refresher training of paramedical staff (Penjor et al 2020). Hence, educational outreach programs must be sustained and not one off-exercises.…”
Section: Strategies For Control Of Dog-mediated Rabies (A) Educational Outreachmentioning
confidence: 99%